VD_FINDINFO Décision / 2017 / 912 vom 1. Februar 2018 - VD Tribunal cantonal (2018)
DIFFAMATION, CALOMNIE, DISJONCTION DE CAUSES, DROIT D'ÊTRE ENTENDU | 173 ch. 1 CP, 173 ch. 2 CP, 174 CP, 29 al. 2 Cst., 30 CPP (CH)